The Relationship Between the Foreign Exchange Regime and Macroeconomic Performance in Eastern Africa - Stotsky, Janet (IMF Working Papers; Working Paper ;, 2012)
This study examines the relationship between the foreign exchange regime and macroeconomic performance in Eastern Africa. The study focuses on seven countries, five of which decisively liberalized their foreign exchange regimes. The study assesses the relationship between (i) growth and various determinants, including the exchange regime, the real exchange rate, and current account liberalization; and (ii) inflation and various determinants, including lagged inflation, the nominal exchange rate, the exchange regime, and liberalization. We find that in our sample, for the determinants of growth, investment and the real exchange rate are significant determinants but not the exchange regime or liberalization; and for inflation, the lagged inflation rate, nominal exchange rate, and the de facto regime are significant. Exchange rate pass-through is limited.